The omnibus film as message picture: cold war politics and the myth of national unity in It's a Big Country (1951). Issue 3 (3rd July 2017) - Chung, Hye Seung; Diffrient, David Scott
Abstract : This essay uncovers the production and reception history ofIt's a Big Country (1951), a multi-director M-G-M film that explores the interwoven issues of nationhood, citizenship and cultural diversity during the cold war era. Produced by the liberal studio chief Dore Schary, who referred to the film as a 'propaganda picture' and a 'message picture, 'It's a Big Country is a contradictory text that explicitly upholds the cold war mandate of inclusive representations (with episodes focusing on different racial/ethnic groups including African-Americans, Italians, the Irish, Greeks, Hungarians and Jews) and implicitly challenges the myth of national unity through subtle textual maneuvers. We argue that the imperfections and shortcomings of Schary's ambitious project (which received negative reviews upon its original release) are indicative of the national failings of a segregated, Cold War America. To a certain extent, the film was ahead of its time and its potential as a meaningful social statement had to be significantly tempered due to industrial and ideological constraints. Its underlying message, however, still has the power to spark conversations about the dialectic of social fragmentation and national belonging as well as the omnibus-like assembly of identities that go into making a nation.